Type 2 Porcine Reproductive and Respiratory Syndrome Virus Infection Mediated Apoptosis in B‐ and T‐Cell Areas in Lymphoid Organs of Experimentally Infected Pigs. Issue 3 (20th May 2012) - Gómez‐Laguna, J.; Salguero, F. J.; Fernández de Marco, M.; Barranco, I.; Rodríguez‐Gómez, I. M.; Quezada, M.; Carrasco, L.
Summary Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) infection is characterized by persisting in lungs and lymphoid tissue, resulting in systemic lymphoid depletion. The aim of this study was to correlate the histological changes, viral antigen expression and apoptosis phenomena in tonsil, medial retropharyngeal and mediastinal lymph nodes of 12 pigs inoculated with a type 2 PRRSV isolate (Chilean strain 2402). Apoptosis phenomena were observed mainly in lymphocytes and secondly in macrophages of lymph nodes and tonsils of inoculated animals, showing a peak of both apoptotic cells and viral antigen expression at the end of the study (21 dpi). However, the number of apoptotic cells was higher than the number of PRRSV‐positive cells at the end of the study. This finding together with the location of apoptotic cells and PRRSV‐positive cells in different structures of lymphoid organs supports the hypothesis that PRRSV‐positive macrophages might modulate the apoptosis phenomena in other cells, mainly lymphocytes, by means of an indirect mechanism. Furthermore, apoptotic cells were detected both in B‐ and T‐cell areas of lymphoid organs, suggesting that apoptosis phenomena may play a role in the impairment of the host immune response during PRRS.